Polymerization of 2, 5‐diaminoterephthalic acid‐type monomers for the synthesis of polyamides containing ladder unit. Issue 14 (3rd May 2017) - Yokoyama, Akihiro; Kuramochi, Jinya; Kiyota, Ryohei; Kishimoto, Kazuki; Takaishi, Kazuto; Yokozawa, Tsutomu
ABSTRACT: To synthesize ladder‐type polyamides by construction of two amide bonds successively, 2, 5‐diaminoterephthalic acid derivatives bearing anthranilic acid ester and isatoic anhydride moieties were synthesized and their polymerization was investigated. Polymerization of the methyl ester monomer proceeded in the presence of lithium hexamethyldisilazide (LiHMDS) as a base in tetrahydrofuran (THF). However, mass spectroscopic analysis of the product suggested that not only the bis(trimethylsilyl)amide anion of LiHMDS but also the methoxide anion eliminated at the second amide‐linkage formation reaction decomposed the isatoic anhydride unit of the growing oligomer by nucleophilic attack to disturb the polymerization. To reduce the nucleophilicity of the eliminated anion, methyl ester of the monomer was changed to phenyl ester and its polymerization was studied. The reaction conditions were optimized, and the best result was obtained when the polymerization was conducted in the presence of 1.0 equivalent of LiHMDS without additives in THF at 50 °C. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2365–2372 Abstract : Base‐promoted polymerization of monomers bearing anthranilic acid ester and isatoic anhydride moieties was studied for the synthesis of ladder‐type polyamide. The polymerization of methyl ester monomer in the presence of lithium hexamethyldisilazide as a base was disturbed by side reactions. In contrast, the polymerization of phenyl ester monomer gave a higher molecular weight product.